The spheroidal trackball: generalising the fixed trackball for virtual camera navigation - González-Toledo, Daniel; Cuevas-Rodríguez, María; Molina-Tanco, Luis; Reyes-Lecuona, Arcadio (Springer Nature, 2024)
Virtual trackball techniques have become a standard in 3D applications, particularly for interfaces with limited degrees of freedom such as touchscreens or mice. The fact that we are used to them does not mean that they cannot be improved upon. Recent research has highlighted the significance of considering users’ mental models of a preferred rotation axis, as it can improve performance, perceived usability and perceived workload. Building upon these findings, this paper introduces the spheroidal trackball framework—a novel method for orbiting the virtual camera around elongated objects. The paper presents the mathematical formulation and the evaluation of the technique. The formulation offers enough information to implement the approach. The evaluation shows the advantages of this approach over the fixed spherical trackball for this class of objects, in terms of task performance, usability and perceived workload. This research constitutes an advancement in the refinement of 3D user interaction techniques, opening new avenues of innovation in this still evolving field.
Keywords: Elipsoides; Realidad virtual; Usability; 3D interaction; 3D user interfaces; Virtual trackball; Virtual camera navigation; Ellipsoid; Spheroid